Antioxidant and Free Radical Scavenging Activity of Various Extracts of Boerhavia diffusa Linn. (Nictaginaceae) - BEHANZIN, GBÉSSOHÈLÈ JUSTIN; MAMA SIROU, Amidou Ibrahima (My University, 2018)
The main objective of this work is to make the phytochemical screening to evaluate the phenolic composition and anti-radical activity of various extracts of Boerhaavia diffusa Linn. that will explain his therapeutic effects. It will characterize the chemical groups, to identify the best solvent extraction of total polyphenols, flavonoids and condensed tannins by testing and modifying the extraction solvents and evaluate in vitro antioxidant activity of n-Hexane, dichloromethane, ethyl acetate, methanol and ethanol extracts from Boerhaavia diffusa trapping method according to the free radical DPPH. Boerhavia diffusa Linn. a plant of the Beninese pharmacopoeia used in traditional medicine in Benin. In this work n-Hexane, dichloromethane, ethyl acetate, methanol and ethanol extracts were prepared from the stem leaves of Boerhavia diffusa Linn. The quantitative estimation of total phenols, tannins and flavonoids by the colorimetric method showed that the extracts are rich in these compounds. Evaluation of antioxidant power was performed using the method of DPPH free radical trapping.
Keywords: Boerhavia diffusa Linn; Free radical scavenging activity; DPPH; total phenols; flavonoids; tannins